Prospective associations of physical fitness with spinal flexibility in childhood: implications for primary prevention of non-specific back pain - Bade, Svea; Lona, Giulia; Infanger, Denis; Endes, Katharina; Roth, Ralf; Faude, Oliver; Hanssen, Henner (Frontiers in Pediatrics, 2023)
Early predictors for back pain need to be identified for the development of prevention strategies starting as early as childhood. For this purpose, the relationship between physical fitness and spinal flexibility at the age of six years and its prediction for the development of non-specific back pain (BP) during childhood were analyzed.In this prospective cohort study with 4-year follow-up, school children from the Swiss Canton Basel-Stadt, aged 6-8 (2014) at baseline and 10-12 years (2018) at follow-up, were recruited from 26 primary schools (n=238) within a mandatory evaluation of motor skills. Data for spinal flexibility were collected by use of a hand-held computer-assisted device and physical fitness was assessed by shuttle run performance at both time points. Occurrence of non-specific BP was determined by use of a questionnaire at follow-up.Children with higher physical fitness at baseline achieved a better spinal flexibility four years later (β [95% CI] 3.75 [2.19-5.3] degree per 1 stage increase, p<0.001). Higher spinal flexibility by 1 degree at baseline was associated with 2% less odds for non-specific BP at follow-up (OR [95% CI] 0.98 [0.97-0.99] per 1 degree increase, p=0.032). There was little evidence for a direct association between physical fitness at baseline and development of non-specific BP at follow-up (OR [95% CI] 1.13 [0.96-1.34] per 1 stage increase, p=0.128).Fitness performance is associated with the development of better childhood spinal flexibility over four years. Moreover, a better spinal flexibility at baseline was associated with less nonspecific BP at follow-up. This study demonstrates suggests that physical fitness may beis a key modulator of spinal flexibility which itself is a main determinant of non-specific BP during childhood development. Further long-term studies are warranted to confirm our assumptions and to prove trajectories into adolescents and adulthood.